A multi‐primary empirical model based on a quantum dots display technology. Issue 3 (4th February 2020) - Huraibat, Khalil; Perales, Esther; Viqueira, Valentín; Martínez‐Verdú, Francisco M.
Abstract: In this work, we built a multi‐primary display model based on the new quantum dots (QD) technology to enlarge the display color gamut. In this way, first the emission spectral radiance curves of the three RGB channels of a commercial QD display were fitted to a four‐parameter function. From this modeling, it is possible to gain new theoretical color primaries by selecting new spectral peaks (cyan, yellow, magenta, and/or additional RGB primaries) and imposing some colorimetric conditions for the resulting white of this proposed theoretical multi‐primary display. Proper characterization to assess the performance of the display was conducted to know if the basic "gain‐offset‐gamma" (GOG) model can be used for direct and inverse color reproduction (from RGB to CIE‐XYZ, and vice versa). The GOG model was found to well characterize this display. The spatial uniformity of the display was also evaluated in luminance and color chromaticity terms. Finally, with the primaries modeling and color characterization based on the GOG model, a 5‐primary model (RGBYC) was tested. The evaluation of this theoretical RGBYC display model confirms the gamut enlargement, which can also improve goniochromatic color reproduction.